2021
DOI: 10.1186/s12913-021-06967-3
|View full text |Cite
|
Sign up to set email alerts
|

Parental perception of neonatal transfers from level 3 to level 2 neonatal intensive care units in Calgary, Alberta: qualitative findings

Abstract: Background Retro-transfers from level 3 to 2 NICUs in Alberta’s regionalization of neonatal care system are essential to ensure the proper utilization of level 3 NICUs for complex neonatal cases. Parents often experience distress that relates to the transfer of their neonates to another hospital. Limited information is available regarding parental perceptions of distress during transfers for neonates requiring care between NICUs in the current Canadian context. The objective of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Many studies of NICU transitions have shown that parents need increased support during transitions both from hospital staff and other sources of support in their support network. 2,20 This study expanded on this by describing specifically how parent's own ability to adapt could be improved through support from staff.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies of NICU transitions have shown that parents need increased support during transitions both from hospital staff and other sources of support in their support network. 2,20 This study expanded on this by describing specifically how parent's own ability to adapt could be improved through support from staff.…”
Section: Discussionmentioning
confidence: 99%
“…22,[52][53][54] This paper follows from our previous analysis of managerial systems that organise decisions about place of care-and lead to transfers that are not always clinically necessary and very often burdensome for parents. 3 Management systems that organise place of care can have considerable knock-on effects, not only creating stress for parents 10,[37][38][39]55 but also precipitating new work to create continuity amid those place-of-care disruptions. Indeed, within the community of care, parents undertake a significant amount of the work required to maintain continuity for their babies.…”
Section: Discussionmentioning
confidence: 99%